Peripheral tumour targeting using open-source virtual bronchoscopy with electromagnetic tracking: a multi-user pre-clinical study. - Jaeger, Herman Alexander; Trauzettel, Fabian; Nardelli, Pietro; Daverieux, Federico; Hofstad, Erlend Fagertun; Leira, Håkon O.; Kennedy, Marcus P.; Langø, Thomas; Cantillon-Murphy, Pádraig (Minimally Invasive Therapy & Allied Technologies, 2019)
Objectives: The goal was to demonstrate the utility of open-source tracking and visualisation tools in the targeting of lung cancer. Material and methods: The study demonstrates the first deployment of the Anser electromagnetic (EM) tracking system with the CustusX image-guided interventional research platform to navigate using an endobronchial catheter to injected tumour targets. Live animal investigations validated the deployment and targeting of peripheral tumour models using an innovative tumour marking routine. Results: Novel tumour model deployment was successfully achieved at all eight target sites across two live animal investigations without pneumothorax. Virtual bronchoscopy with tracking successfully guided the tracked catheter to 2–12 mm from the target tumour site. Deployment of a novel marker was achieved at all eight sites providing a reliable measure of targeting accuracy. Targeting accuracy within 10 mm was achieved in 7/8 sites and in all cases, the virtual target distance at marker deployment was within the range subsequently measured with x-ray. Conclusions: Endobronchial targeting of peripheral airway targets is feasible using existing open-source technology. Notwithstanding the shortcomings of current commercial platforms, technological improvements in EM tracking and registration accuracy fostered by open-source technology may provide the impetus for widespread clinical uptake of electromagnetic navigation in bronchoscopy.